How much does labour turnover cost? A case study of Kenyan Small and Medium Tour - Wambugu, Angeline Wambui (Machakos University, 2019)
The hospitality industry is a service-based industry, which is highly dependent on a customer-focused approach, and a motivated and knowledgeable workforce. Any shift in human capital therefore is viewed as detrimental as its long term success. Research postulates that employee mobility is a major cost and leakage of human capital. In addition, studies have shown that labour turnover affects organizational performance, customer quality and employee productivity. Despite the adverse effect of labour turnover on growth, survival and sustainability of organizations in the hospitality industry, there is limited research on turnover costs. This paper provides an understanding of the turnover rates and direct financial costs of labour turnover in small and medium tour operators. A descriptive research design was used. Primary data was collected using a self- administered questionnaire. Stratified sampling and simple random sampling technique were used to select 30 respondents. The target populations comprised of human resource managers and owner/managers of small and medium tour operators, which are registered with the Kenya Association of Tour Operators and operating in Nairobi and its environs. The study findings indicated that tour operators experienced acute turnover rates, which are much higher than the average turnover rate in service industries. The study findings also revealed substantial replacement costs are attributed to labour turnover in small and medium tour operators. The implications of these findings for managerial practice and suggestions for further research are discussed.
Keywords: Labour turnover; Turnover costs; Tour operators; SMEs; Kenya